2017
DOI: 10.3389/fpls.2017.01843
|View full text |Cite
|
Sign up to set email alerts
|

Combined Genomic and Genetic Data Integration of Major Agronomical Traits in Bread Wheat (Triticum aestivum L.)

Abstract: The high resolution integration of bread wheat genetic and genomic resources accumulated during the last decades offers the opportunity to unveil candidate genes driving major agronomical traits to an unprecedented scale. We combined 27 public quantitative genetic studies and four genetic maps to deliver an exhaustive consensus map consisting of 140,315 molecular markers hosting 221, 73, and 82 Quantitative Trait Loci (QTL) for respectively yield, baking quality, and grain protein content (GPC) related traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 86 publications
(128 reference statements)
2
78
1
1
Order By: Relevance
“…A map showing the genomic regions significantly associated with yield-related traits was created with MapChart software version 2.3 (Voorrips, 2002). Finally, a comparison between the chromosomic location of SNP markers significantly associated with phenotypic traits in this study and those previously reported was performed using the released genome sequence of hexaploid wheat (IWGSC et al, 2018) and the integrated map of Quraishi et al (2017) for markers whose sequence was not available.…”
Section: Marker-trait Association Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A map showing the genomic regions significantly associated with yield-related traits was created with MapChart software version 2.3 (Voorrips, 2002). Finally, a comparison between the chromosomic location of SNP markers significantly associated with phenotypic traits in this study and those previously reported was performed using the released genome sequence of hexaploid wheat (IWGSC et al, 2018) and the integrated map of Quraishi et al (2017) for markers whose sequence was not available.…”
Section: Marker-trait Association Analysismentioning
confidence: 99%
“…To compare the chromosome location of significant SNP markers found in this study with those previously reported, we used the annotated reference wheat genome and the integrated map reported by Quraishi et al (2017), which includes simple sequence repeats (SSRs), restriction fragment length polymorphisms (RFLPs), diversity arrays technology (DArT), genes, and SNP markers. Wheat grain yield is determined not only by the genes directly controlling yield and yield components, but also by the genes controlling plant development and maturity.…”
Section: Association Mapping and Comparison With Previous Researchmentioning
confidence: 99%
“…However, despite the importance of genetic dissection of this complex trait, only a few QTL studies have been reported in wheat using bi-parental mapping populations (Guo et al, 2012;Kong et al, 2013;Zhao et al, 2014;Gong et al, 2015). Genetic maps used in these various studies can be integrated at one place to identify consensus genomic region called Meta-QTL (MQTL), independent of population type and genotype/ environment interaction (Quraishi et al, 2017). This approach of identifying MQTL by meta-analysis was first proposed by Goffinet and Gerber (2000), and has since been applied in many crops including wheat (Griffiths et al, 2009;Gegas et al, 2010;Quraishi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…GPC QTLs were reported previously for each chromosome of tetraploid and hexaploid wheat (Quraishi et al 2017). Similarly, we detected GPC QTLs in 10 out of 14 chromosomes of tetraploid wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis, using high resolution SNP-based map, expanded the number of loci with contribution of WEW alleles from 8 to 14 (Fatiukha et al 2019b). The identification of common or meta-QTLs between independent populations can help to improve QTL interval confidence, as demonstrated by Quraishi et al (2017), and can be used for confirmation of detected effects in different genetic backgrounds. Nevertheless, the identification of co-located QTLs among the large number of publications is restricted by the absence of consensus positions for many of the published markers.…”
Section: Discussionmentioning
confidence: 99%